How has the pandemic affected social media use and mental health? - Morić, Sandra; Mudrov, Emira; Kostić Valčić, Jelena (Archives of Pharmacy, 2022)
The aim of the study was to explore patients' attitudes about using social networks during the pandemic and the impact of the pandemic on mental health in Croatia, Bosnia and Herzegovina and Serbia. The research was conducted in December 2021 on a sample of 303 patients. The questionnaire was delivered to the patients by the pharmacists, electronically and contained 16 questions of which, the most important  were:Has the Covid-19 pandemic increased the need to use social media? Have you searched a social network for a recommendation for herbal preparation for calming/sleeping?(1)The findings were following: When asked what feelings the pandemic caused, 95 respondents answered that they feel good, while the rest were accompanied by depression, anxiety, fatigue, difficulty in relaxing or concentrating. The majority of respondents (79.9%) said that the pandemic affected the increase in time spent on social networks, and 128 of them used social networks as a source of health advice. The reason for concern was the neglected awareness of the importance of maintaining mental health during the Covid-19 pandemic (2), with which the majority of respondents (90.8%) agreed. Approximately one third of the respondents rated their health condition as good, while 68.7% had some kind of disorder or difficulty related to mental health. The obtained results show that the pandemic greatly affected people's mental health and caused an increase in the use of social networks.